THE EFFECT OF SERVICE QUALITY AND COST ON RETENTION MEDIATED BY SATISFACTION(STUDY ON SLTA KEBANGSAAN) - Yunianto; C. Tarumingkeng, Rudy (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
This study aims to analyse the effect of service quality and tuition fees on student satisfaction and retention at SLTA Kebangsaan. The method used was descriptive quantitative through a questionnaire survey of 100 selected students. The results showed that service quality (facilities, teaching, and administrative services) and tuition fees have no direct effect on student retention. However, both factors significantly increase student satisfaction, which in turn has a positive impact on retention. The key finding of this study reveals that satisfaction acts as a full mediator in the relationship between service quality-cost and retention. The practical implications of this study emphasise the importance of schools prioritising increasing student satisfaction through service quality improvements and cost policy adjustments, as satisfaction is a key determinant in building students' long-term loyalty. This study provides a strategic contribution for school managers in formulating more effective student retention policies